Head and Body Dyskinesia During Gait in Tactical Athletes With Vestibular Deficit Following Concussion - Fraser, John J.; VanDehy, Jacob; Bodell, Dawn M.; Gottshall, Kim R.; Sessoms, Pinata H. (Frontiers in Sports and Active Living, 2021)
Background: Vestibular deficit is common following concussion and may affect gait. The purpose of this study was to investigate differences in head and pelvic center of mass (COM) movement during gait in military tactical athletes with and without concussion-related central vestibular impairment. Material and Methods: 24 patients with post-concussion vestibular impairment (20 males, 4 females; age: 31.7 ± 7.9 years; BMI: 27.3 ± 3.3) and 24 matched controls (20 males, 4 females; age: 31.8 ± 6.4 years; BMI: 27.2 ± 2.6) were included in the analyses. Three-dimensional head and pelvic displacement and velocities were collected at a 1.0 m/s standardized treadmill walking speed and assessed using Statistical Parametric Mapping t-tests. Maximum differences (dmax) between groups were reported for all significant kinematic findings. Results: The Vestibular group demonstrated significantly diminished anteroposterior head excursions (dmax = 2.3 cm, p = 0.02) and slower anteroposterior (dmax = 0.37 m/s, p = 0.01), mediolateral (dmax = 0.47 m/s, p = 0.02) and vertical (dmax = 0.26 m/s, p < 0.001) velocities during terminal stance into pre-swing phases compared to the Control group. Vertical pelvic excursion was significantly increased in midstance (dmax = 2.4 cm, p = 0.03) and mediolaterally during pre- to initial-swing phases (dmax = 7.5 cm, p < 0.001) in the Vestibular group. In addition, pelvic velocities of the Vestibular group were higher mediolaterally during midstance (dmax = 0.19 m/s, p = 0.02) and vertically during post-initial contact (dmax = 0.14 m/s, p < 0.001) and pre-swing (dmax = 0.16 m/s, p < 0.001) compared to the Control group. Significance: The Vestibular group demonstrated a more constrained head movement strategy during gait compared with Controls, a finding that is likely attributed to a neurological impairment of visual-vestibular-somatosensory integration.